LUMBUNG VILLAGE ASSETS MANAGEMENT SYNERGY - Ihsan Rahman Fauji; Tatang Parjaman; Diwan Pramulya; Aditiyawarman; Candra Firmanto (JGSRD: Journal of Government Science and Rural Development, 2022)
Lumbung Village is one of the villages in Lumbung District, Ciamis Regency which has a fairly large area with various assets owned. However, asset management is still not optimally as it should be. By building synergies between existing parties, it is hoped that stakeholders can work together in managing village assets so that existing assets can be managed optimally to encourage village independence and progress as well as community welfare. The purpose of this study, namely to determine the synergy between the Village Government and BUMDes in managing village assets in Lumbung Village, Lumbung District, Ciamis Regency. The research method used is descriptive qualitative. The results of the research that the authors get are that there are still constraints in terms of budget and media and communication facilities in terms of managing village assets. Thus, the management of village assets by the Village Government and Village Owned Enterprises (BUMDEs) is still not running optimally.